Comparative morphology of the male terminalia of the subtribe Rhinotorina (Diptera, Heleomyzidae, Rhinotorini) - Almeida, Julia C.; Ale-Rocha, Rosaly (Zootaxa, 2011)
The Rhinotorini (Diptera, Heleomyzidae) are currently divided into three subtribes, which were considered as monophyletic groups. Rhinotorina, the main focus of this study includes Rhinotora Schiner, Apophoneura Malloch, Neorhinotora Lopes, and Rhinotoroides Lopes. This study is aimed to provide a hypothesis of homology among the structures of the male terminalia of the four genera of Rhinotorina, as well as to reassess the diagnostic features proposed by D. McAlpine for the subtribe, and to furnish new information about the morphology of these structures, particularly of the hypopygium. Species of the four genera of Rhinotorina were studied, as well as species of other subtribes of Rhinotorini. The putative synapomorphies for the Rhinotorina stated by D. McAlpine are considered here to be consistent, being observed in the four genera included in the present study. The hypopygium in Rhinotorina, in contrast, is very variable, and the study of its structures has added only one diagnostic feature to Rhinotorina: the presence of a ventral plate on the hypandrium. The degree of variation is not equivalent among the structures of the hypopygium: the surstyli are the most variable structures in Neorhinotora, and are very useful to diagnose species, and the shape of the epandrium, bacilliform sclerites, cerci, phallus, ejaculatory apodeme, phallapodeme, and hypandrium are very conservative in this genus. In Rhinotora, on the other hand, whereas the cerci, surstyli, phallus, phallapodeme, and postgonites vary widely among the species, the shapes of the bacilliform sclerites and the ejaculatory apodeme are relatively constant. The comparisons made among the male terminalia of Rhinotorina suggest that this set of structures is a promising source of informative characters for future phylogenetic studies of Rhinotorini and Heleomyzidae.